Нормативно-правова база функціонування історичної освіти в педагогічних ВНЗ Львова (1944–1957 рр.) - Антоняк, Ірина; Antonyak, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2017)
The influence and ideological control of the Soviet authorities on the historical educational sphere, as well as providing it with more ideological than scientific significance for integrating the history of Ukraine into the Soviet-style historical model of the education of students in the spirit of «Soviet patriotism» is investigated. The reasons, conditions and consequences of the introducing certain regulatory documents for the historical pedagogical education of the post-war Lviv are considered. У публікації здійснено спробу комплексного аналізу нормативно-правової бази історичної освіти, на яку впродовж 1944-1957 рр. опиралися педагогічні інститути Львова (Львівський державний педагогічний інститут та Учительський інститут). Розглянуто причини, умови й наслідки впровадження певних нормативно-правових документів для педагогічної історичної освіти повоєнного Львова.
Regulatory Base of the Functioning of Historical Education in the Pedagogical Institutions of Lviv (1944-1957)
Keywords: нормативно-правова база; педагогічні інститути Львова; історична освіта; навчальна та ідейно- виховна робота; regulatory base; educational institutions of Lviv; historical education; educational and ideological- educational work